Case Report Mediastinal Teratoma Resembling Vascular Tumor with Rapid Growth Accompanied by Vena Cava Superior Syndrome and Bilateral Paramalignant Pleural Effusion - Rini, Ni Made; Pratiwi, Suryanti Dwi; Bayuadi, Imam Suseno; Erawati, Dini Rachma; Yudhanto, Hendy Setyo (Malang Respiratory Journal, 2020)
Background: Teratomas are tumors originate from germ cells, consist of well differentiated tissue from more than one of three layers of embryonic cells: ectoderm, mesoderm and endoderm. Teratomas are generally slow-growing and asymptomatic. Mediastinal teratoma is the most common extra-gonadal germ cell tumor. Superior vena cava syndrome and bilateral paramaligant pleural effusion are complications which can occur in mediastinal teratomas. Case: We report a 37-year-old woman presented with shortness of breath since 1 month before admission, chest pain, cough, weight loss,  swolen of face, neck, and right arm. Chest x-ray showed mediastinal tumor. However, no mediastinal tumor had been detected by chest x-ray to examine her heart disease 3 years earlier. Chest computed tomography scan showed anterosuperior mediastinal tumor surrounding great blood vessels and bilateral pleural effusion. Computed tomography guided transthoracic fine needle aspiration biopsy revealed  tumor containing mature squamous epithelial component. Patient underwent open biopsy by sternotomy and histological assessment confirmed the diagnosis as mediastinal teratoma with vascular lesions predominantly resembling vascular tumor.Conclusion: Establishing the diagnosis of mediastinal teratoma is challenging and it requires multi modality approaches.  Keywords: Mediastinal teratoma, vena cava superior syndrome, bilateral paramalignant pleural effusion.